Arsenic trioxide in the treatment of acute promyelocytic leukemia - Wiktor Jędrzejczak, Wiesław (Contemporary Oncology/Współczesna Onkologia, 2001)
Arsenic trioxide solely or in combination may induce complete remission in virtually all cases of acute promyelocytic leukemia, that currently remains its only clinical indication. Contrary to some expectations when administered intravenously it has only mild adverse effects. Arsenic trioxide acts through induction of apoptosis and differentiation and influences also cells with high expression of multidrug resistance genes. Its precise place in the treatment of acute promyolocytic leukemia is still under investigation. Similarly, a search for other neoplasms sensitive to its action continues.